Paeoniflorin alleviates liver injury in hypercholesterolemic rats through the ROCK/AMPK pathway - Tong Liu; Ning Zhang; Lingya Kong; Sijie Chu; Ting Zhang; Guangdi Yan; Donglai Ma; Jun Dai; Zhihong Ma; Zhihong Ma (Frontiers Media S.A., 2022)
Paeoniflorin (PF) is the main active component in Paeonia lactiflora Pall, and it has multiple effects. However, the precise mechanism of PF in hypercholesterolemia is unclear. In this study, rats were either fed a high-cholesterol diet (HCD) for 4 weeks to establish the hypercholesterolemic model or administered normal saline or PF (20 mg/kg/day). PF significantly reduced liver weight and the liver index. PF reduced hepatic lipid deposition and inflammation, improved serum lipid metabolism, and significantly inhibited serum and hepatic oxidative stress and the inflammatory response. PF treatment caused a marked decrease in the phosphorylated myosin phosphatase target subunit (p-MYPT)-1, nuclear sterol regulatory element-binding protein-1c (SREBP-1c), fatty acid synthase (FAS) levels, and an increase in the low-density lipoprotein receptor (LDLR) and phosphorylated-AMP-activated protein kinase (p-AMPK). Thus, PF could alleviate liver injury in hypercholesterolemic rats, and the specific mechanism may be related to the antioxidant, anti-inflammatory properties, and ROCK/AMPK/SREBP-1c signaling pathway.